SISTEM UJIAN ONLINE CALON MAHASISWA BARU BERBASIS ILEARNING EDUCATION MARKETING PADA PERGURUAN TINGGI - Meta Amalya Dewi; Dede Cahyadi; Yunita Wulansari (CCIT Journal, 2014)
The development of increasingly advanced technology in support of services that can be accessed in various ways in an easy , fast efficient , anytime and anywhere . Services that were once only done face to face (face to face ) started to turn into a more modern and sophisticated as electronic services which can be done relatively efficiently , effectively and quality . Therefore making an application service system that is precise and accurate support is needed for the marketing department to provide good service to prospective new students . With a line -based method , system service entrance exam ( USM ) Prospective New Student ( CMB ) will be very easy to do anywhere and not have to come to campus . The iRangers is a support system in the implementation of the entrance exam Prospective New Student online . Where highly supportive of service in Higher Education Campus Raharja be Featured in IT . In this article is described on issues that arise as well as solving the problem under study . In addition there are distinctive features and advantages of this application . In the implementation shown prtotoype view of application iRangers . It can be concluded that the contribution iRangers system can maximize marketing activities in serving new students to conduct online entrance examination . So the results of research more focused and interesting , and can be used as media and information services that are good for the entire private candidates raharja and society in general